Negative refractive index shaped lens for mobile base station / Salbiah Ab Hamid ... [et al.] - Ab Hamid, Salbiah; Yamada, Yoshihide; Ibrahim, Idnin Pasya; Abd Rahman, Nurul Huda (Universiti Teknologi MARA, 2021)
Recently, there are rapid developments in antenna researches to fulfil the advanced mobile technology requirement including 5G technology. Narrow beam width, higher frequency, and higher gain are among the key characteristics in 5G antenna technology to serve a massive number of users, consistent interconnectivity, and higher capacity. Previously, the multi-beam operation was performed by using array antennas, however, in the 5G system, more losses due to complex feeding network is expected if the conventional array antenna is adopted. Therefore, the lens antenna is identified as one of the potential candidates to replace the current antenna structure used in the mobile base station. In this study, the characteristics of the negative refractive index shaped lens using the energy conservation law in mobile base station applications are investigated. One of the significant findings from this study is that a smaller radius and slender lens configuration can be achieved using a negative refractive index. A lens antenna with the gain of 27.55dB and narrow beam width of 7.81o is produced. This configuration is suitable for mobile base station application due to its less bulky characteristics which makes it easy to be mounted on the base station.